2003
DOI: 10.1038/sj.ijo.0802156
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain and postpartum behaviors associated with weight change from early pregnancy to 1 y postpartum

Abstract: OBJECTIVES: (1) To describe the relative importance of gestational weight gain, postpartum exercise, food intake and breastfeeding to weight change from early pregnancy to 1 y postpartum; and (2) to identify subgroups of women at greatest risk for major weight gain surrounding childbearing. Design: A prospective cohort study of women who registered for obstetrical care in a hospital and primary care clinic system serving a 10 county area of upstate New York. Subjects: A total of 540 healthy adult women who gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
284
0
29

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 345 publications
(329 citation statements)
references
References 29 publications
16
284
0
29
Order By: Relevance
“…Most studies included primarily adult women. 23,[27][28][29][31][32][33]35,36,38,43,46 Four studies reported a mean age above 30 years, 23,27,28,36,46 one study below 20 years. 42 Two studies did not provide any information on their population's age 24,44 (Table 1).…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies included primarily adult women. 23,[27][28][29][31][32][33]35,36,38,43,46 Four studies reported a mean age above 30 years, 23,27,28,36,46 one study below 20 years. 42 Two studies did not provide any information on their population's age 24,44 (Table 1).…”
Section: Qualitative Resultsmentioning
confidence: 99%
“…Tables 1-3 summarize the results of the qualitative analysis. Fifteen prospective studies, 23,24,[29][30][31][32][33][34][35][36]38,[40][41][42][43][44][45] five retrospective studies, 22,[25][26][27][28]37,46 and the control group from a randomized controlled trial 39 were included in the final analysis. Studies in which women were recruited around the time of delivery and then followed prospectively for postpartum body weight (ambivalent design, as baseline weight was assessed retrospectively) 24,29,30,[34][35][36][44][45][46] were considered as prospective in design, as we wanted to focus on the development of postpartum weight change.…”
Section: Qualitative Resultsmentioning
confidence: 99%
See 3 more Smart Citations